Contributions and thoughts on Community Psychology training in regions of Peru - Velázquez Castro, Tesania (2017)
Peru has undergone significant economic growth, but inequality between different groups still exists. In order to improve the training of professionals in Peruvian regions, the Master’s Program in Community Psychology at the Pontificia Universidad Católica del Perú has developed different training programs in Cusco, Ayacucho and Huancavelica. These are excluded regions affected by social violence due to past conflict. This article describes and analyzes the characteristics and the impact of training programs on participants and the population. Furthermore, this article reflects on how to develop vocational training to foster and recreate knowledge in a way that avoids reproducing relations of domination. The con tribution of Community Psychology is highlighted, as well as the professional, political and personal training in Community Psychology.